COVID-19 and Therapeutic Apheresis - Tselmin, Sergey; Julius, Ulrich; Jarzebska, Natalia; Rodionov, Roman N. (Hormone and Metabolic Research, 2022)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, is an unprecedented challenge for the global community. The pathogenesis of COVID-19, its complications and long term sequelae (so called Long/Post-COVID) include, in addition to the direct virus-induced tissues injury, multiple secondary processes, such as autoimmune response, impairment of microcirculation, and hyperinflammation. Similar pathological processes, but in the settings of neurological, cardiovascular, rheumatological, nephrological, and dermatological diseases can be successfully treated by powerful methods of Therapeutic Apheresis (TA). We describe here the rationale and the initial attempts of TA treatment in severe cases of acute COVID-19. We next review the evidence for the role of autoimmunity, microcirculatory changes and inflammation in pathogenesis of Long/Post COVID and the rationale for targeting those pathogenic processes by different methods of TA. Finally, we discuss the impact of COVID-19 pandemic on patients, who undergo regular TA treatments due to their underlying chronic conditions, with the specific focus on the patients with inherited lipid diseases being treated at the Dresden University Apheresis Center.
Keywords: COVID-19; therapeutic apheresis; long/post-COVID syndrome